Commande d’une Centrale PV Connectée au Réseau Via un Onduleur à Source d’Impédance - BOULEHIA Ahmed Madani; BABAGHAYOU Siham; Mr. MOKRANI Lakhdar (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2022)
This memoir presents a study concerning a photovoltaic system connected to the electrical network via an impedance source inverter (Z-Source). This power conditioner allows the PV generator voltage boosting and the control of the powers injected into the grid at the same time. The first part is devoted to the photovoltaic generator, its components, its operating principle, its characteristics and its modeling. Next, the Z-Source inverter has been compared to the voltage and current source inverters. Then, the different topologies and control strategies of this power conditioner have been presented. In addition, the MPPT control by the Conductance Increment (CI) method as well as the control of the powers injected into the grid, through the adjustment of the DC bus voltage and the active and reactive currents, have been described and elaborated. This PV plant has been simulated using MATLAB/SIMULINK software. Several simulations have been carried out in order to show the contribution of the Z-Source converter to improve the quality of energy injected into the grid for different operating conditions corresponding to variable light intensity and temperature.
OPTION : Électrotechnique Industrielle